Kajian Nilai Pendidikan dalam Kakawin Ramayana Sargah I:4 - Ni Putu Purniari (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2021)
The form of Balinese literature is basically a pattern of transformation of Balinese literature. Balinese literature is a collection of fictional works in Balinese and Old Javanese (Kawi). Of course, these fictional works contain imaginative elements (kakawian) created by the creativity of Balinese and Old Javanese authors (poets). Balinese literature has various types and can then be classified into kakawin, parwa (kanda), kidung, babad, geguritan, peparik, wewangsalan, satua, short stories, novels, and modern Balinese poetry. In terms of storyline, Kekawin Ramayana also has differences with Ramayana Walmiki. At the end of the story, when Rama and Sita return to Ayodya, they separate again, so Rama and Sita do not live together, according to Walmiki's version. In the Javanese version, Rama and Sita live together in Ayodya.